REVISITING ASIAN CHURCH: A Critical Analysis of FABC at Forty Years: Responding to the Challenges of Asia - A New Evangelisation in the Light of the Contemporary Developments in Theology - Thiyagarajan, Sathish Kumar (Asian Horizons, 2016)
On the occasion of its fortieth year anniversary, FABC gathered its 10th plenary assembly to evaluate and renew its commitment to the triple dialogue with the poor, cultures and religions. As a fruit of the assembly, they released a document titled FABC at Forty Years which summarised the findings and suggestions of the assembly. The document is significant as it gives a broader spectrum of the foundations and charisma of the Asian Church. Moreover, it is inspiring and instructive as it attempts novel analyses of the global issues by summing them into 15 megatrends. However, when we examine the assembly’s analyses of these mega trends, we may realise that document is in want of a comprehensive understanding of the issues and normative/concrete recommendations. This article attempts to make an overarching summary of the document critically exposing the document’s analyses of global issues and its recommendations in the context of contemporary developments in theology/philosophy.